Agricultural extension - where next? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Extension services established since independence have generally failed to live up to expectations. Increases in agricultural production in ACP countries have been achieved largely through the expansion of the cultivated land area and increased...